Bounds on the effective behavior of a homogenized generalized Reynolds equation - Dag Lukkassen; Annette Meidell; Peter Wall (Journal of Function Spaces and Applications)
We study upper and lower bounds for estimating the effective behavior described by homogenizing a problem which is a generalization of the Reynold equation. All cases when these bounds coincide are also found.